Risk Factors of Cardiovascular Disease among Hypertensive Patients: A Study in A Tertiary Care Hospital in Bangladesh - Haldar, Ganesh Chandra; Hoque, AKM Aminul; Das, Aparna; Mazumder, Ripon Chandra; Karmakar, Pijush (Eastern Medical College Journal, 2024)
Background: Identifying the risk factors for cardiovascular disease (CVD) in hypertensive patients is crucial in cardiovascular research and public health. Hypertension is a major CVD risk factor and uncovering additional contributors to cardiovascular risk in hypertensive individuals is vital for prevention and treatment. Aim of the study: This study aimed to assess the risk factors of cardiovascular disease among hypertensive patients. Methods: This prospective observational study was conducted at the Department of Medicine, Eastern Medical College & Hospital, Cumilla, Bangladesh from July 2022 to June 2023. In this study, 95 hypertensive patients were included as the study subjects, and they were selected by purposive sampling technique. Data was collected using a semi-structured pre-designed questionnaire and data analysis was carried out using MS Office tools. Results: Among the participants, it was observed that hyperlipidemia was present in 83% of the cases as the most common risk factor. Additionally, physical inactivity (51.6%), obesity (46.3%), and smoking (44.2%) were identified as risk factors in more than 40% of cases. Some participants also had a family history of cardiovascular diseases (22.1%), diabetes mellitus (14.7%) and hypothyroidism (3.2%). Conclusion: Among hypertensive patients, the most common risk factors for cardiovascular disease include hyperlipidemia, physical inactivity, obesity and smoking. Patients in this group should also be aware of additional risk factors such as a family history of cardiovascular diseases, diabetes mellitus and hypothyroidism. Eastern Med Coll J. July 2023; 8 (2): 29-32